URGENSI GOOD SAMARITAN LAW DALAM MEMBERIKAN PERLIDUNGAN HUKUM BAGI MASYARAKAT DALAM MEMBANTU SITUASI KEDARURATAN MEDIS - NIM. A1011221231, HERI WICAKSONO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The absence of a norm that explicitly protects lay first responders in medical emergencies creates legal uncertainty and a chilling effect that hinders public involvement in providing first aid. This study aims to analyze the urgency of establishing a Good Samaritan Law (GSL) and formulate the basic principles that need to be adopted in its design. Using a juridical-normative method with primary and secondary legal materials, this study finds that the GSL is necessary to provide good faith-based immunity, establish a reasonable care standard according to the capacity of lay first responders, and limit protection against acts of gross negligence. The results also demonstrate the importance of strengthening public education and emergency system coordination. In conclusion, the GSL is urgently needed as a legal instrument that guarantees the protection of first responders, strengthens social solidarity, and increases the effectiveness of the initial response to medical emergencies in Indonesia. Keywords: Good Samaritan Law; Medical Emergencies; First Aid Protection Abstrak Ketiadaan norma yang secara tegas melindungi penolong awam dalam keadaan darurat medis menimbulkan legal uncertainty dan chilling effect yang menghambat keterlibatan masyarakat dalam pemberian pertolongan pertama. Penelitian ini bertujuan menganalisis urgensi pembentukan Good Samaritan Law (GSL) dan merumuskan prinsip dasar yang perlu diadopsi dalam perancangannya. Menggunakan metode yuridis-normatif dengan bahan hukum primer dan juga bahan hukum sekunder, penelitian ini menemukan bahwa GSL diperlukan untuk memberikan imunitas berbasis good faith, menetapkan standar reasonable care sesuai kapasitas penolong awam, serta membatasi perlindungan terhadap tindakan gross negligence. Hasil penelitian juga menunjukkan pentingnya penguatan edukasi publik dan koordinasi sistem darurat. Kesimpulannya, GSL mendesak dirumuskan sebagai instrumen hukum yang menjamin perlindungan penolong, memperkuat solidaritas sosial, dan meningkatkan efektivitas respons awal kedaruratan medis di Indonesia. Kata Kunci: Good Samaritan Law, Kedaruratan Medis, Perlindungan Penolong